Cognitive science: What one needs to know. - Peterson, Gregory R. (Zygon: Journal of Religion & Science)
Focuses on cognitive science which is a developing paradigm that informs and involves several disciplines, including artificial intelligence, and neuroscience among others. How this science studies the mind; Effects of developments in this science on the mind; Areas of religious import in which the cognitive sciences need to be taken into account.